SKILL DEVELOPMENT FOR ECONOMIC INDEPENDENCE: ENTREPRENEURSHIP STRATEGIES AMONG TECHNOLOGY AND VOCATIONAL EDUCATION STUDENTS IN EBONYI AND ENUGU STATES - Ngozi Johnson, Dr. Cynthia; Okoro, Prof. Emmanuel Chukwudi (Top Educational Review Journal (TERJ), 2023)
Entrepreneurship plays a pivotal role in determining the economic trajectory of societies, distinguishing between development and underdevelopment. This study delves into the essence of entrepreneurship, emphasizing its role as a process to identify and harness market opportunities while managing associated risks for sustained gains. The creative and innovative nature of entrepreneurship enables its adaptation to address immediate community needs, as highlighted by Onoh (2013). Siaka's (2004) perspective further underscores entrepreneurship as the creation of novel, valuable entities through the dedication of time, effort, finances, and willingness to undertake risks, ultimately reaping both monetary rewards and personal gratification. Anugwom (2007) enriches this discourse by defining entrepreneurship as a dynamic engagement with business risks, driven by a fluid environment and pursued with a profit-oriented mindset. Recognizing the significance of education in comprehending the multifaceted dimensions of entrepreneurship, this study advocates for its essential role in shaping entrepreneurial understanding. Through the identification of business prospects, proactive actions, and the realization of rewards, entrepreneurship emerges as a mechanism to navigate the evolving economic landscape. By exploring these definitions and perspectives, this study highlights the integral relationship between entrepreneurship and education in fostering economic growth and societal progress.